Development of an Asymmetric Cellulose Acetate-Ionic Liquid P6,6,6,14[Phos] Gel Membrane for the Perstraction of Succinic Acid from a Model Fermentation Solution of Yarrovia Lipolytica - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E (Elsevier B.V., 2025)
This study introduces a novel approach to separate succinic acid (SA) from fermentation mixtures using an asymmetric membrane based on the gelation of the ionic liquid [P6,6,6,14][PHOS] coated with two layers of cellulose acetate. The membrane was designed to explore the synergistic effect of polymer-ionic liquid interfaces according to the solution-diffusion theory. The gelation of the ionic liquid was achieved using 12-hydroxystearic acid at a concentration of 1.5%, allowing the use of ionic liquid gels as new materials for the generation of membranes. The perstraction performance of the membrane was evaluated over 5 h at two different temperatures (25°C and 37°C), with an initial feed solution concentration of 50 kg m−3 for SA and glycerol and pure water as a receiving phase., Several flow rates and phase-volume ratios were studied anda mass transfer model based on the resistance-in-series theory was assessed to understand the behavior of each mass transfer stage considering the distribution in each interphase. Interestingly, optimal perstraction results were obtained at 37°C, with an average transmembrane flux of 0.22 kg m-2h−1 for SA, an extraction percentage of 43.1% for SA and 0.7% for glycerol, and a SA/glycerol selectivity of 54.98. Besides presenting a novel composite membrane, this study reports pioneering perstraction outcomes, highlighting its potential as an innovative SA separation strategy and structured new materials for selective extractions. © 2024 Elsevier B.V.